Making sense of spirituality in nursing and health care practice : an interactive approach - McSherry, Wilfred (J. Kingsley, 2006)
Caring for the spiritual needs of patients is a highly significant yet often neglected and misunderstood aspect of health care. This results, in part, from a general lack of guidance and instruction given to healthcare professionals on the subject. This new edition of an established introductory guide to spirituality and health care practice draws extensively on case studies illustrating the application of theory to practice. It encourages the exploration, through reflective activities, of what spirituality means, both to patients and to the healthcare professionals caring for them. This book.